Vinyl boronate polymers with dynamic exchange properties. Issue 46 (15th November 2022) - Dong, Jin; He, Congze; Xu, Chaoran; Yun, Jie; Pan, Xiangcheng
Abstract : This work introduces vinyl boronic acid and its pinacol ester derivative as suitable monomers in radical polymerization to prepare well-defined polyolefins with boron-containing groups that show sol–gel transition properties. Abstract : Boron-containing polymers have aroused great research interest in materials science due to their specific recognition, stimulus-response, and dynamic exchange. However, the introduction of boron-containing groups into the pendant of polymers remains a great challenge. This work introduces vinyl boronic acid (VB(OH)2, CH2 CHB(OH)2 ) and a series of boronate monomers for preparing well-defined polyolefins with boron-containing groups. Vinylboronic acid pinacol ester (VBpin ) was found to be a suitable monomer in radical polymerization, and the well-defined corresponding polymers were successfully obtained by reversible addition–fragmentation chain transfer (RAFT) polymerization. The thermal stability of the prepared VBpin -containing polymers showed a significant improvement after the reduction of the trithioester end groups. Moreover, the dynamic exchange properties of VBpin polymers were investigated, indicating the potential of these polymers as functional materials.